The Recovery Of Assets Results Of Corruption Through Additional Criminal Payment Of Replacement Money - Hery Purwanto; Siti Ummu Adillah (Law Development Journal, 2021)
This study aims to identify and examine efforts to recover assets resulting from criminal acts of corruption through additional criminal payments of replacement money. This study uses a normative juridical approach, which is descriptive analysis. The data used is secondary data obtained through literature study, which is then analyzed qualitatively. The results of this study are efforts to recover assets resulting from criminal acts of corruption through additional criminal payments of replacement money based on the provisions of Article 18 paragraph (1) letter b of Act No. 31 of 1999 jo. Act No. 20 of 2001. The purpose of imposing additional penalties is to ensure that state financial losses caused by actions can be recovered to the state through the imposition of additional penalties for payment of compensation. The judge in deciding the amount of additional criminal payment of compensation to the defendant based on legal facts at trial that prove the amount of property obtained by the defendant from the crime of corruption.